Exploring the Adoption Rate of ISO 50001 in the Finnish Industry : A Comparative Analysis with Germany - Miri Beidokhti, Mojtaba (My University, 2024)
This study examines the adoption of ISO 50001 in the Finnish industrial sector, comparing it with Germany to understand the implementation gap. Drawing from data collected through the European Manufacturing Survey (EMS) consortium and a comprehensive literature review, the research investigates the drivers, barriers, and implications of ISO 50001 certification. Key findings reveal a significant disparity in adoption rates between Germany and Finland, with Germany exhibiting a penetration rate over 1600% higher than Finland. While financial incentives, environmental responsibility, and alignment with corporate strategy emerge as key drivers for adoption, challenges such as limited financial resources, weak leadership commitment, and cultural barriers hinder implementation efforts. The study underscores the importance of targeted policies and initiatives to address barriers and promote ISO 50001 adoption. Additionally, insights from case studies demonstrate substantial reductions in energy consumption and greenhouse gas emissions post-certification, highlighting the potential for significant environmental and financial benefits. Suggestions for further research include expanding the sample size, exploring the impact of direct incentives on adoption, comparing it with other energy management standards, and conducting longitudinal studies on energy performance. By pursuing these avenues, organizations can enhance their energy management practices, reduce environmental impact, and realize long-term cost savings.
Keywords: Sustainability, Energy management system, ISO 50001, EnMS certification, Energy consumption reduction, ISO 14001